Green separation of bromelain in food sample with high retention of enzyme activity using recyclable aqueous two-phase system containing a new synthesized thermo-responsive copolymer and salt. (1st June 2019) - Wang, Lei; Li, Wenxuan; Liu, Yuanyuan; Zhi, Wenjing; Han, Juan; Wang, Yun; Ni, Liang
Graphical abstract: Highlights: A thermo-responsive polymer was synthesized with specified molecular weight and LCST. The novel recyclable aqueous two-phase system have been constructed for the first time. Excellent phase splitting ability and separation efficiency were exhibited in the ATPS. The ATPS manifested highly preserved activity in the purification of bromelain. Abstract: High cost and enzyme deactivation in purification process are the two main obstacles for the use of enzyme as green catalyst. The objective of this work was to overcome these limitations by developing a cost-effective aqueous two-phase system (ATPS) for efficient purification of enzymes with remarkable separation efficiency and high retention of enzyme activity. The ATPS was formed by thermo-responsive block copolymer PEG113 -b-PNIPAM149 and salt as phase-forming components combining economy, recovery and sustainability. This strategy fabricated block copolymer with specified molecular weight and low LCST, which not only achieved better phase splitting but also ensured easy recycling for block copolymer. The developed ATPS demonstrated excellent extraction and biocompatibility for bromelain in real sample with 94.87% separation efficiency and 77.06% activity, which were remarkably higher than those obtained in EOPOEO-based ATPS. The recycling of copolymer was introduced to minimize cost, with recovery efficiency of 90% in the five cycles.